THE MODELING OF STRESS STATE OF LANDSLIDES WITH COMPLEX STRUCTURE BY COMPLEX VARIABLE BOUNDARY ELEMENT METHOD TAKING ACCOUNT THE SEISMICITY - MELKONIAN, D.; CHERKEZ, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
An analytical-numerical technique the complex variable boundary element method is applied for landslides stress state plain problem solution, and also for estimation of their stability taking account the filtrational weighing and seismicity. The isolines of normal, tangential stresses and of stability are constructed inside of investigated slope.